SACO: un algoritmo de clustering espacial con hormigas inteligentes - Dib Ashur, José (2016)
Bio-inspired algorithms have received much attention in recent years, because they allow to discover, quickly and efficiently, knowledge and patterns in large databases. In this work, a new algorithm based on the behaviour of ant colonies to discover clusters in spatial databases is presented. The algorithm proposed was evaluated using several well-known test instances and compared its performance considering other proposals from the literature.